Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1007/s40336-022-00512-w
|View full text |Cite
|
Sign up to set email alerts
|

Association of chest CT severity score with mortality of COVID-19 patients: a systematic review and meta-analysis

Abstract: Purpose Chest computed tomography (CT) is a high-sensitivity diagnostic tool for depicting interstitial pneumonia and may lay a critical role in the evaluation of the severity and extent of pulmonary involvement. In this study, we aimed to evaluate the association of chest CT severity score (CT-SS) with the mortality of COVID-19 patients using systematic review and meta-analysis. Methods Web of Science, PubMed, Embase, Scopus, and Google Scholar were used to search for primary articles. The meta-analysis was p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 47 publications
(21 reference statements)
1
14
2
Order By: Relevance
“…Yuan et al (11) reported that patients with pulmonary involvement have a higher mortality rate. A metaanalysis including 7,106 COVID-19 patients also showed that thorax CT involvement in these patients could predict mortality (12). In accordance with the literature, our results showed a higher mortality rate with pulmonary involvement.…”
Section: Discussionsupporting
confidence: 91%
“…Yuan et al (11) reported that patients with pulmonary involvement have a higher mortality rate. A metaanalysis including 7,106 COVID-19 patients also showed that thorax CT involvement in these patients could predict mortality (12). In accordance with the literature, our results showed a higher mortality rate with pulmonary involvement.…”
Section: Discussionsupporting
confidence: 91%
“…The outcome supports the hypothesis that CT-SS and COVID-19 mortality are directly correlated. There are greater mortality probabilities for COVID-19 patients with higher CT severity scores [20].…”
Section: Discussionmentioning
confidence: 97%
“…Interestingly, it was observed that the deceased patients had higher levels of leukocytes, neutrophils, and markers of inflammations, while the levels of lymphocytes and haemoglobin were significantly lower in relation to the patients who recovered [ 13 ]. Computed tomography revealed a higher degree of lung involvement in deceased patients [ 14 ]. Some studies indicate that the degree of lung involvement in unvaccinated patients is considerably higher than in those vaccinated with two doses of COVID-19 vaccines [ 15 ].…”
Section: Discussionmentioning
confidence: 99%